Hubungan Etos Kerja Islami Terhadap Kepuasan Bekerja Dan Kinerja Karyawan Pada Unit Pegadaian Syariah Blauran - Habibie, Rizky Firdaus (Universitas Negeri Surabaya, 2020)
The purpose of this research is to determine what work satisfactions and employee’s performances dealings with Islamic work ethics on Subdivision of Pegadaian Syariah Blauran. This research uses quantitative research methods with an associative approach. The number of samples taken were 43 respondents whom were employees of the Subdivision of Pegadaian Syariah Blauran. Data collection techniques in this study used a questionnaire and measured with a Likert scale and then processed and analyzed with the IBM SPSS Statistics 23 application. The result of this research explains that Islamic work ethics have stronger relation with employee’s performance than work satisfaction. Islamic work ethics has correlation of 0,657 toward work satisfaction. Meanwhile, Islamic work ethics has correlation of 0,725 toward employee’s performance.